Creep of VT1-0 alloy in different structural states - Savchuk, E.S.; Sokolenko, V.I.; Karaseva, E.V.; Mats, A.V.; Mats, V.A.; Frolov, V.A. (Вопросы атомной науки и техники, 2022)
The effect of electrons irradiation with an energy of E = 10 MeV and a dose of D = 5·10¹⁹ сm⁻² on the structure evolution and creep of alloy VT1-0 in initial and nanostructured states obtained by the IPD method has been stud-ied. It is shown that, the deformation nanostructure of VT1-0 is resistant to subsequent deformation under creep conditions at T = 20 °C and is destroyed at T = 350 °C due to the development of recrystallization processes. Irradi-ation by electrons with an energy of E = 10 MeV and a dose of D = 5·10¹⁹ сm⁻² has slightly effect on the mechanical characteristics of VT1-0, both in initial and nanostructured states, but leads to the conservation and stabilization of the nanostructure during creep at T = 20 °C and to the deceleration of the process of structure transformation at T = 350 °C as a result of a decrease in the level of internal stresses. Вивчено вплив електронного опромінення з енергією E = 10 МеВ і дозою D = 5·10¹⁹ сm⁻² на еволюцію стру-ктури та повзучість сплаву ВТ1-0 у стані постачання і наноструктурном стані, отриманого методом ІПД прокаткою. Показано, що деформаційна наноструктура стійка до подальшої деформації в умовах повзучос-ті при Т = 20 °C і руйнується при Т = 350 °C внаслідок розвитку процесів рекристалізації. Опромінення елек-тронами з енергією E = 10 МеВ i дозою D = 5·10¹⁹ сm⁻² слабо впливає на механічні характеристики ВТ1-0 як у стані постачання, так і в наноструктурному стані, проте призводить до збереження і стабілізації наностру-ктури в процесі повзучості при Т = 20 °C і до уповільнення процесу трансформації структури при Т = 350 °C у результаті зниження рівня внутрішніх напружень. Изучено влияние электронного облучения с энергией E = 10 МэВ и дозой D = 5·10¹⁹ сm⁻² на эволюцию структуры и ползучесть сплава ВТ1-0 в состоянии поставки и наноструктурном состоянии, полученном методом ИПД прокаткой. Показано, что деформационная наноструктура устойчива к последующей дефор-мации в условиях ползучести при Т = 20 °C и разрушается при Т = 350 °C вследствие развития процессов рекристаллизации. Облучение электронами с энергией E = 10 МэВ и дозой D = 5·10¹⁹ сm⁻² слабо влияет на механические характеристики ВТ1-0 как в состоянии поставки, так и в наноструктурном состоянии, однако приводит к сохранению и стабилизации наноструктуры в процессе ползучести при Т = 20 °C и замедлению процесса трансформации структуры при Т = 350 °C в результате снижения уровня внутренних напряжений.